(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
This thesis examines the theoretical models of educational quality management in non-state higher education institutions. It provides a comparative analysis of classical and contemporary quality management models, explores their applicability in the context of non-state higher education, and identifies the key factors influencing the effectiveness of quality assurance systems. The study emphasizes the unique characteristics of non-state institutions, including their organizational flexibility, market orientation, and resource constraints. Based on a review of international and national experiences, the thesis proposes an integrative model tailored to the specific needs of non-state higher education.